Phagocytic Uptake of Nosema bombycis (Microsporidia) Spores by Insect Cell Lines - Shun-feng CAI; Xing-meng LU; Hai-hong QIU; Ming-qian LI; Zhen-zhen FENG (Journal of Integrative Agriculture, 2012)
Microsporidia are highly specialized obligate intracellular parasites that can infect a wide variety of animals ranging from protists to mammals. The classical concept of the parasite invasion into a host cell involves its polar tube acting as a needle-syringe system. However, recent studies show microsporidian spores can also gain access to host cells by phagocytosis. The present study investigated the phagocytic uptake process of causative agent of the pebrine disease, Nosema bombycis, in several insect cell lines. We observed KOH-treated spores and cold-storaged spores can be easily uptaken by all the studied cell types 4 h post inoculation. In contrast, large numbers of freshly recovered spores remained in the culture medium. To further investigate the intracellular fates of KOH-treated spores and cold-storaged spores, electron and fluorescence microscopy were performed. No intracellular germination or subsequent parasite development were observed. Intracellular spores can be detected in host cells by polyclonal antibody 7 d post inoculation, suggesting phagocytized N. bombycis could not be digested by these non-professional phagocytes. Our results suggest that, phagocytic uptake of N. bombycis spores might represent a defense mechanism of the host cells and the intact spore wall barrier enable freshly recovered spores to keep resistance to this mechanism.